Augmented Reality to Interior Design Company Performance - Septiyanti, Septiyanti (Journal of Applied Information, Communication and Technology, 2019)
Interior design is an industrial company that works of flow from visual drawing into implementation construction of interior design drawing on site as a framework to fulfilled demand of client needed. Each day interior design company market becomes more high competitiveness as a national or even as a global market, and demand to fulfill with adequately performance to reach global market. In this report depart from previous comprehension; augmented reality can be a purpose effort interior design application for environment experience from computing interaction.